Expression of a thermostable xylanase gene from Bacillus coagulans ST-6 in Lactococcus lactis - Abdul Rahim, Raha; Chang, Li Yen; Sipat, Abdullah; Mohd Yusoff, Khatijah; Toosa, Haryanti (The Society for Applied Microbiology, 2006)
Aims: The aim of the study is to evaluate whether xylanase can be used as a potential reporter gene for cloning and expression studies in Lactococcus.